Evaluasi Sistem Billing Pasien Dalam Rangka Meningkatkan Efektivitas Operasional Rawat Jalan - Iriyadi, Iriyadi; Budianto, Enjang Tachyan (Jurnal Ilmiah Kesatuan (JIK), 2009)
Billing System is important for the hospitals. This System can help them to run the activities, in managing data, this system is able to process many dataâs which are useful for the hospital management. This system is also able to give information in processing the revenues. The objective of this research is to find out the billing system for outpatient and procedure system for outpatient at PMI Hospital Bogor. Also to find out the role of billing system in increasing the ffectiveness of hospital operating system in managing the revenues. The research was carried out at PMI Hospital, located in Jalan Pajajaran Bogor, and it serves medical services for the patient. The research has proven that PMI Hospital Bogor uses Fully Integrated Bill System, it is a billing system which is integrated to all systems in the hospital (especially for financial issues). In this system all of the processes, such as registration, polyclinics actions, pharmacy and all supporting things will be recorded directly, even finance and Accounting departments will get reports and dataâs easily and quickly. The result of evaluation shows that each system need to be evaluated in its implementation in order to be able to full fill all the users need. At PMI Hospital, billing system for the outpatient is more able to answer the management needs in providing report, mainly the revenues of outpatient. The system is more efficient in putting dataâs or transactions compare to manual input. But, there is a weakness of the system, the report of the revenues does not match with data transactions provided. The solution is the report is made into manual recapitulation which is reported as the revenues report later.